Increasing Student’s Correspondence Course Study Result with Development of Adobe Flash Android-Based Media - Devi Artha Bonita; Sarbini -; Maimunah - (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
The purpose of this study is to produce an Adobe Flash-based Android learning media on subjects that have tested the feasibility of the media through validation testing increased students result. This type of research is research and development (R&D). This product is validated by material experts, media experts, and small groups and have been tasted in the experimental class. The results showed the development of Adobe Flash-based learning media Android is a significant improvement of students result.